Acute performance and physiological responses to repeated‐sprint exercise in a combined hot and hypoxic environment - Yamaguchi, Keiichi (Physiol Rep, 2020)
We investigated performance, energy metabolism, acid–base balance, and endocrine responses to repeated‐sprint exercise in hot and/or hypoxic environment. In a single‐blind, cross‐over study, 10 male highly trained athletes completed a repeated cycle sprint exercise (3 sets of 3 × 10‐s maximal sprints with 40‐s passive recovery) under four conditions (control [CON; 20℃, 50% rH, FiO(2): 20.9%; sea level], hypoxia [HYP; 20℃, 50% rH, FiO(2): 14.5%; a simulated altitude of 3,000 m], hot [HOT; 35℃, 50% rH, FiO(2): 20.9%; sea level], and hot + hypoxia [HH; 35℃, 50% rH, FiO(2): 14.5%; a simulated altitude of 3,000 m]). Changes in power output, muscle and skin temperatures, and respiratory oxygen uptake were measured. Peak (CON: 912 ± 26 W, 95% confidence interval [CI]: 862–962 W, HYP: 915 ± 28 W [CI: 860–970 W], HOT: 937 ± 26 W [CI: 887–987 W], HH: 937 ± 26 W [CI: 886–987 W]) and mean (CON: 808 ± 22 W [CI: 765–851 W], HYP: 810 ± 23 W [CI: 765–855 W], HOT: 825 ± 22 W [CI: 781–868 W], HH: 824 ± 25 W [CI: 776–873 W]) power outputs were significantly greater when exercising in heat conditions (HOT and HH) during the first sprint (p < .05). Heat exposure (HOT and HH) elevated muscle and skin temperatures compared to other conditions (p < .05). Oxygen uptake and arterial oxygen saturation were significantly lower in hypoxic conditions (HYP and HH) versus the other conditions (p < .05). In summary, additional heat stress when sprinting repeatedly in hypoxia improved performance (early during exercise), while maintaining low arterial oxygen saturation.